2004
DOI: 10.1118/1.1696708
|View full text |Cite
|
Sign up to set email alerts
|

A new algorithm for determining collimator angles that favor efficiency in MLC based IMRT delivery

Abstract: A new algorithm to determine collimator angles that favor delivery efficiency of intensity modulated radiotherapy plans was developed. It was found that the number of segments and monitor units (MUs) were largely reduced with the set of collimator angles determined with the new algorithm without compromising plan quality. The improvement of delivery efficiency using the new algorithm depends on the size and shape of the target(s), the number of modulation levels, and the type of leaf-sequencing algorithm. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Use of anatomy-based segments with each beam angle combination has also been considered (Beaulieu et al 2004a(Beaulieu et al , 2004b. Optimization of collimator angle should also not be overlooked as the orientation of the multileaf collimator has an impact on the efficacy of the IMRT treatment plan (Wang et al 2004a).…”
Section: Introductionmentioning
confidence: 99%
“…Use of anatomy-based segments with each beam angle combination has also been considered (Beaulieu et al 2004a(Beaulieu et al , 2004b. Optimization of collimator angle should also not be overlooked as the orientation of the multileaf collimator has an impact on the efficacy of the IMRT treatment plan (Wang et al 2004a).…”
Section: Introductionmentioning
confidence: 99%
“…It was evident that non-0 17,19,20 Wang et al found that the number of MUs was largely reduced without compromising plan quality when collimator angles were determined with a new algorithm. 30 Furthermore,…”
Section: Discussionmentioning
confidence: 99%
“…In 30 Furthermore, Milette suggested that comparable dose distributions and better delivery efficiency were possible with the rotating aperture optimization technique. 31 Additionally, the innovation of the current study was that it proposed to adopt MATLAB to write code, combined with analytical methods to obtain the best collimator angle (CLx) in gastric cancer for the first time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The beam isocenter in the treated plans was positioned automatically by the TPS at the center of the tumor. The collimator angle was determined so that the movement direction of HDMLC (high definition MLC) aligning with the minimum dimension of the target for best conformal plan . The treated plans were created with the intention to have more uniform dose in the target and the conventional P‐IDL (averagely (91.7 ± 0.5, ±1.7)% of the maximum dose.…”
Section: Methodsmentioning
confidence: 99%